Influence of number of contact efforts on running performance during game-based activities - Johnston, R. D.; Gabbett, T. J.; Jenkins, D. G. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To determine the influence the number of contact efforts during a single bout has on running intensity during game-based activities and assess relationships between physical qualities and distances covered in each game. Methods: Eighteen semiprofessional rugby league players (age 23.6 ± 2.8 y) competed in 3 off-side small-sided games (2 × 10-min halves) with a contact bout performed every 2 min. The rules of each game were identical except for the number of contact efforts performed in each bout. Players performed 1, 2, or 3 × 5-s wrestles in the single-, double-, and triple-contact game, respectively. The movement demands (including distance covered and intensity of exercise) in each game were monitored using global positioning system units. Bench-press and back-squat 1-repetition maximum and the 30-15 Intermittent Fitness Test (30-15IFT) assessed muscle strength and high-intensity-running ability, respectively. Results: There was little change in distance covered during the single-contact game (ES = -0.16 to -0.61), whereas there were larger reductions in the double- (ES = -0.52 to -0.81) and triple-contact (ES = -0.50 to -1.15) games. Significant relationships (P < .05) were observed between 30-15IFT and high-speed running during the single- (r = .72) and double- (r = .75), but not triple-contact (r = .20) game. Conclusions: There is little change in running intensity when only single contacts are performed each bout; however, when multiple contacts are performed, greater reductions in running intensity result. In addition, high-intensity-running ability is only associated with running performance when contact demands are low.